Star formation and molecular hydrogen in dwarf galaxies: a non-equilibrium view - Hu, Chia-Yu; Naab, Thorsten; Walch, Stefanie; Glover, Simon; Clark, Paul C. (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. We study the connection of star formation to atomic (H i) and molecular hydrogen (H2) in isolated, low-metallicity dwarf galaxies with high-resolutio
Gesehen am 20.05.2020